Simulation & data validation of small-scale LNG system - Roslina, Sapuan (2008)
Liquefaction of natural gas is a process where the natural gas was condensed to a liquid through a cooling process and the original volume of natural gas is being converted into liquefied natural gas by a factor of more than 600 which allows for its efficient transport and storage. There are three basic types of liquefaction methods, which are i) classic cascade cycle, ii) cascade cycle with mixed coolant and iii) decompression cycle with a turbo-expander. However, mixed-refrigerant (MR) process is preferred, because the MR process is simple, low equipment count and can reduce hydrocarbon inventory. The study is based on Cao et al. (2005), where the flowsheet showed incomplete process data. Based on this, the material and energy (M&E) balance can not be established. Such establishment is important to analyze the performance of the existing LNG system and to propose appropriate modification. The objective of this study is to overcome the problem arise in the Cao’s system by simulate and validating the result from MRC process. For this study, the method of analysis that will be used is the structural decomposition approach. This method has been chosen because it is difficult to converge the LNG exchanger units without enough or complete process data. With this approach, a simulation of the system can be done by using the HYSYS software, which includes the use of Peng-Robinson (PR) and Lee-Kesler-Plocker (LKP) equations of states. Also, the other method that has been applied is sum square error (SSE). Since simulation and data validation processes are based on estimation, it will produce errors. The first trial with the value for pressure drop of each cooler and heater units is 15 kPa produces the smallest error among other trials. So, the process data in this trial have the highest possibility to represent the MRC in Cao’s system.